Development of nano carbon and conducting polymers based ternary composites for supercapattery / Javed Iqbal - Javed , Iqbal (2020)
Although significant efforts have been devoted on the development of energy storage systems such as batteries and fuel cells in the past decades, the low power density, short cyclic life and high maintenance cost have kept them away from many applications. Alternatively, supercapattery which has the characteristic features of batteries as well as supercapacitors has gained much attention because of its rapid charge/discharge mechanism, long life cycle, and high power density. However, supercapattery generally suffers from poor energy density. This research aims to develop carbon and conducting polymers based ternary nanocomposites for high performance supercapattery. Pristine metal oxide nanostructures suffer from high particle aggregations which lead to decrease the electrochemically active sites, therefore, conducting matrices are used to develop the nanocomposites. In this work, hydrothermal route was used to develop ternary nanocomposites of metal oxide (cobalt oxide, Co3O4), noble metals (silver (Ag) and gold (Au)) and carbonaceous matrices such as multiwalled carbon nanotubes (MWCNTs), reduced graphene oxide (rGO) as well as conducting polymers such as polypyrrole (PPy) and polyaniline (PANI). The synthesized ternary nanocomposites were characterized by various analytical techniques. The electrochemical performances were studied through cyclic voltammetry, galvanostatic charge-discharge and electrochemical impedance spectroscopy techniques. In the first system, ternary nanocomposites of multiwalled carbon nanotubes intercalated with cobalt oxide nanograins and decorated with silver nanoparticles (NPs) were synthesized and used for supercapattery application. The fabricated device Ag/Co3O4@MWCNTs//activated carbon (AC) delivered maximum energy and power density values of 16.50 Wh kg-1 and 297.50 W kg-1, respectively. In the second system, gold nanoparticles were used instead of silver to synthesize the ternary nanocomposite (Au/Co3O4@MWCNTs) to check the effect on the device performance by changing the noble metal. The supercapattery device demonstrated splendid cycling stability with a retention value of 91.90 % in 1 M KOH (potassium hydroxide) electrolyte for over 3500 cycles with an energy density of 18.80 Wh kg-1 at a power density of 302.00 W kg-1. In the third system, ternary nanocomposite was synthesized with rGO instead of MWCNTs and evaluated its (Ag/Co3O4@rGO) performance as positive electrode material in supercapattery. The assembled devices found to deliver the highest energy density 23.63 Wh kg-1 at a power density of 440.00 W kg-1. In the fourth system, polypyrrole was used as a conducting platform to synthesize the ternary nanocomposite and subsequently used to develop two electrodes assembly (Ag/Co3O4@PPy//AC). The resultant device achieved the maximum energy density of 24.79 Wh kg-1 with the corresponding power density, 554.40 W kg-1. In the fifth system, polypyrrole was replaced with polyaniline to develop ternary nanocomposite, i.e., Ag/Co3O4@PANI. The fabricated device (Ag/Co3O4@PANI//AC) based on ternary nanocomposite deliver energy density and power density, 14.01 Wh kg-1 and 165.00 W kg-1, respectively. From the obtained results, it can be understood that all the five systems incorporated with carbonaceous matrices and conducting polymers as a conducting platform produced excellent results. This work ventures the frontiers of carbonaceous materials and conducting polymers based ternary nanocomposites for energy storage devices.